1996
DOI: 10.1159/000237374
|View full text |Cite
|
Sign up to set email alerts
|

Participation of lnterleukin-5 and lnterleukin-8 in the Eosinophil Migration Induced by a Large Volume of Saline

Abstract: Recently we demonstrated that the eosinophil migration into rat peritoneal cavities induced by a large volume of saline is mediated by LTB4 released by the resident macrophages and mast cells. In the present study, we have investigated the involvement of IL-5 and IL-8 in this process. We observed that saline-stimulated mast cells released the eosinophil chemotactic cytokines IL-5 and IL-8, while macrophages released only IL-8. These observations were confirmed by the ability of antibodies against IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This finding was unexpected, however, as previous work has demonstrated that LPS administration is associated with eosinophil infiltration [29]. LPS activation of macrophages has been shown to result in the expression of eosinophil chemoattractants [33, 34] and depletion of these cells has been associated with inhibition of tissue eosinophilia [31]. Furthermore, IL‐18 has been shown to induce the expression of GM‐CSF, an important eosinophil‐related cytokine, from these cells [8].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was unexpected, however, as previous work has demonstrated that LPS administration is associated with eosinophil infiltration [29]. LPS activation of macrophages has been shown to result in the expression of eosinophil chemoattractants [33, 34] and depletion of these cells has been associated with inhibition of tissue eosinophilia [31]. Furthermore, IL‐18 has been shown to induce the expression of GM‐CSF, an important eosinophil‐related cytokine, from these cells [8].…”
Section: Discussionmentioning
confidence: 99%
“…Other doses of IL‐5 (20 and 50 ng/ml), Rantes (1 and 3 ng/ml) and TNF‐α (20 and 100 IU/ml) also did not stimulate the nitrite production either alone or in the presence of LPS. This absence of effect of these cytokines is not consequence of species specificity, since the same batch of IL‐5, Rantes and TNF‐α induced eosinophil migration ( Oliveira et al . 1996 ) and hyperalgesia (personal observation) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies demonstrated saline induced migration of eosinophils into peritoneum mediated by LTB4 that was released by resident mast cells and macrophages [5]. This process appears to be mediated either by IL-5 inducing a specific eosinophilic migration, or by IL-8 inducing a mixed migration of eosinophils and neutrophils [16]. BAL differential cell count from our study population showed significant amounts of neutrophils, suggesting the possibility of an IL-8 mediated process.…”
Section: Discussionmentioning
confidence: 55%